A Case of Lymphoma Simulating Primary Sternal Tumour - Sahin, Atalay (EL-MED-Pub, 2014)
Any mass on the chest wall may not always be the primary local pathology. A case of lymphoma with an aggressive course may involve the sternum through local invasion and can mimic a chest wall tumour. A 15-year-old boy with mediastinal lymphoma presented with a sternal mass. Partial sternectomy with replacement by methyl methacrylate prosthesis was performed.